KEMAMPUAN AUDITOR INTERNAL DALAM MENGUNGKAP FRAUD PADA TRANSAKSI PEMBELIAN - Sari, Eka Novita; Ardini, Lilis (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2017)
ABSTRACTThis research is meant to find out the skill which is owned by auditors to disclose fraud particularly in recording of purchase transaction at PT. X also to find out the auditors procedure in avoiding and detecting fraud at PT. X. the research method of this research uses qualitative method because this research does not meant to prove a hypothesis, meanwhile the data analysis technique has been done by using descriptive analysis with qualitative approach. Based on the result of analysis and the discussion, the fraud of purchase recording can be anticipated with the existence of a good internal control. In order to support the auditor to disclose the fraud of purchase recording, a skill that is compatible with SPAP which is categorized into three aspects i.e.: general standard, field work standard, and report standard are required. In conducting the purchase transaction recording at PT. X, auditor has found a fraud elements, it can be seen from goods purchase transaction of the 400Gr aluminum packaging foil and sacks of raw coal. Auditor skill is used to disclose the fraud of purchase transaction recording at PT. X by using field work standard.Keywords: Audit, Fraud, Purchase